Attitudes and Perceptions of Police Officers in Boston, Chicago, and Washington, DC, 1966 - Reiss, Albert J. Jr ([Verlag nicht ermittelbar], 1989)
This survey was designed to explore perceptions and attitudes of police officers in three metropolitan areas toward their work and the organizations and publics with which they interact. Issues of interest include (1) the nature of police careers and police work, and officers' satisfaction with their jobs, (2) officers' orientations toward policing tasks and their relationships with the public, and (3) officers' perceptions of organizations and systems that influence or change police work.